A phenomenological approach for structure-property relationship of polybasic cryogels based on n-alkyl methacrylate esters: Anion-specific effect on swelling kinetics and elasticity. (29th April 2019) - Tanc, Beril; Orakdogen, Nermin
Abstract: Stimuli-responsive weakly cationic cryogels and hydrogels of poly( N, N -dimethylaminoethyl methacrylate) PDMAEMA with diethyleneglycol dimethacrylate (DEGDMA) as crosslinking agent have been synthesized at various gel-preparation concentrations as new alternative ion-responsive networks via free radical crosslinking (cryo)polymerization conducted at different temperatures. The influence of the reaction parameters; the gel-preparation concentration and the polymerization temperature on the equilibrium swelling degree, swelling kinetic parameters and basic structural properties of PDMAEMA cryogels (Cgs) and hydrogels (Hgs) were investigated. The specific-anion response of prepared PDMAEMA gels to a range of potassium salt solutions; KCl, KBr and KI was evaluated in the range of ionic-strength between 10 −5  M and 1.0 M. To determine the associative interactions between PDMAEMA network-surfactant species and the optimum conditions necessary to induce surfactant binding, the extent of swelling in aqueous medium was studied in the presence of different types of surfactants; CTAC, CTAB and SDS. The oscillating swelling processes of both PDMAEMA Cgs and Hgs followed the Schott second order dynamic equation. The water diffusion followed by non-Fickian mechanism with anomalous behavior was alternatively viewed as the probe to understand the influence of the gel composition and the gel-preparation concentration on the microstructure of homopolymeric polybasic gels. The specific ion-responsivity and ability of binding surfactant species give these intelligent PDMAEMA Cgs and Hgs wide potential in bio-sensing applications. Graphical abstract: Weakly polybasic cryogels and hydrogels based on n -alkyl methacrylate esters have been synthesized at various gel-preparation concentrations as new alternative ion-responsive networks via free radical crosslinking (cryo)polymerization conducted at different temperatures.Image 1 Highlights: New ion-responsive networks prepared by free radical crosslinking (cryo)polymerization. Formation of porous network and the thicker pore walls in PDMAEMA cryogels. Specific ion-responsivity and ability of binding surfactant species were investigated. Variation in elasticity of PDMAEMA cryogels and hydrogels against ionic-strength change. Porous structure of PDMAEMA cryogels facilitated non-Fickian water diffusion.